Carrageenan-induced ulceration of the large intestine in the guinea pig. Issue 2 (February 1971) - Watt, J.; Marcus, R.
Abstract : A 5% aqueous solution of degraded carrageenan derived from the red seaweed Eucheuma spinosum was fed to guinea pigs in their drinking water over a period of 20-45 days. Occult blood in the faeces and multiple ulcers in the caecum, colon and rectum occurred in 100% of animals by the 30th day. The clinical and pathological features bear a close resemblance to human ulcerative colitis. The method provides a simple experimental model for the study of various aspects of the pathology of ulcerative lesions in the large intestine as well as the effects of therapeutic agents.